Modified catalyst and preparation method thereof, polyolefin elastomer and preparation method and application thereof

By using a modified catalyst in the gas-phase polymerization process, the light transmittance of the polyolefin elastomer is improved, the problem of low light transmittance in the prior art is solved, the application quality and proportion of it in photovoltaic films is improved, and the application quality and proportion of it is expanded. The prospects for industrial application.

CN119285815AActive Publication Date: 2025-01-10XINJIANG DUSHANZI PETROCHEMICAL CO LTD +1

Patent Information

Application Number
CN202411846920.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-01-10
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

The polyolefin elastomers produced by the existing gas phase polymerization process have low light transmittance, which affects their application proportion and quality stability in photovoltaic films.

Method used

Modified catalysts, including metallocene catalyst matrix and low-carbon olefin homopolymer coating, form a coating layer through micropolymerization reaction, inhibit catalyst activity, promote uniform distribution of comonomers on the ethylene molecular chain, and improve light transmission. Rate.

Benefits of technology

It significantly improves the light transmittance of polyolefin elastomers, improves their application quality and proportion in photovoltaic adhesive films, and makes its industrial application prospects more broad.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a modified catalyst and a preparation method thereof, a polyolefin elastomer and a preparation method and application thereof, the modified catalyst comprises a catalyst matrix and a coating layer coating the outer surface of the catalyst matrix, the metallocene catalyst comprises a zirconocene chloride main catalyst and a butyl aluminoxane cocatalyst, and the coating layer is made of a low-carbon olefin homopolymer. According to the polyolefin elastomer prepared by the method, the uniformity of a comonomer inserted into a molecular chain segment is improved, and the light transmittance of a product is improved, so that the polyolefin elastomer has a wider industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polyolefin elastomers, and in particular to a modified catalyst and a preparation method thereof, a polyolefin elastomer and a preparation method and application thereof. Background Art

[0002] The preparation process of polyolefin elastomer (POE) is to introduce a large amount of comonomer, i.e. α-olefin, into the ethylene main chain, disrupting the original crystal state and forming more short side chains, which makes the polymer tend to "plasticization effect". This reduces the crystallinity of ethylene on the side chains, giving the material better optical properties. Moreover, POE has the advantages of low volume resistivity, low water vapor permeability, good aging resistance, and low potential induced decay (PID). It is generally produced with EVA (ethylene and vinyl acetate copolymer) by three-layer co-extrusion casting method. EPE structure (EVA-POE-EVA) film or pure POE film.

[0003] At present, the proportion of POE in the raw materials of photovoltaic module encapsulation film is 20~30%, and there is room for further improvement. With the advancement of photovoltaic technology, photovoltaic modules will be dominated by N-type batteries in the future, and the module type will develop from single-glass single-sided power generation to double-glass double-sided power generation. Different types of batteries and modules require corresponding packaging materials. EPE film and POE film are indispensable packaging materials for new batteries in the future. The continued growth in the global demand for photovoltaic modules will lead to a significant increase in the demand for EVA and POE packaging materials.

[0004] From the application perspective, in order to ensure the high photoelectric conversion efficiency of photovoltaic power generation components, photovoltaic films must have high transmittance. According to the energy industry standard "NB / T10200-2019 Polyolefin Elastomer (POE) Encapsulation Insulation Film for Crystalline Silicon Solar Cell Modules", the transmittance of POE film at 290~380nm is required to be ≥70%, and the transmittance at 380~1100nm is required to be ≥90%. The actual procurement quality requirements of photovoltaic film companies for POE are 290~380nm transmittance ≥85%, and 380~1100nm transmittance ≥90%. POE for photovoltaic films is currently produced by solution polymerization and gas phase polymerization. The stable and mature POE for photovoltaic films in the market generally has a high transmittance, while solution POE with poor quality stability or gas phase POE with high density may have insufficient transmittance. The density is 0.8750~0.8880g / cm 3Taking the vapor-phase POE in the range as an example, affected by factors such as microstructure, the full-band transmittance (0.5mm sample) is generally 84~88%, which seriously affects its application ratio in photovoltaic film POE, making the advantages of low production cost and low product odor of vapor-phase POE unable to be brought into play. In addition, vapor-phase POE with low transmittance may have high melting point micro-components, which cannot be effectively plasticized within the processing temperature range of photovoltaic film, causing holes in the prepared photovoltaic film or excessive crystal points, resulting in quality incidents.

[0005] In the prior art, the Chinese invention patent publication number is: CN118221858A discloses a method for preparing a polyolefin elastomer POE for photovoltaic encapsulation, and ethylene, comonomers, organic solvents, main catalysts and co-catalysts are added to a polymerization stirring reactor under anhydrous and oxygen-free conditions to react to obtain an elastomer POE, which is a solution process production. The Chinese invention patent publication number is: CN116789883A discloses a polyolefin elastomer and its application in photovoltaic encapsulation film. The elastomer preparation step clearly states that the solvent is mixed with α-olefin and then injected into the reactor, which is a solution polymerization process; the composition prepared by the elastomer is used for photovoltaic encapsulation film and has better optical properties, electrical insulation properties and anti-PID properties. The Chinese invention patent publication number is: CN116041598A discloses an olefin polymer for photovoltaic film and a solution polymerization method thereof, which obtains an olefin polymer for photovoltaic film with improved anti-PID properties. The Chinese invention patent publication number is: CN115746746A discloses a polyolefin elastomer composition for photovoltaic encapsulation film, and the polyolefin elastomer is obtained by solution polymerization. Through analysis, the relationship between the POE structure and the performance of the polyolefin elastomer composition is found, thereby ensuring that the light transmittance, water vapor permeability, volume resistivity and other properties of the polyolefin elastomer composition remain at a high level. The Chinese invention patent publication number is: CN117567961B discloses an ethylene / α-olefin random copolymer for photovoltaic film and its application. The copolymer has a fast crosslinking speed and high crosslinking degree in the application of photovoltaic film, and the light transmittance of the photovoltaic film is high; it is clarified that the copolymer is prepared by a kettle reactor and a solution polymerization process.

[0006] Based on this, in the above-mentioned prior art content, POE for photovoltaic film is mainly produced by solution polymerization process, which is relatively complicated and cumbersome. However, POE produced by gas phase polymerization process has the defect of low light transmittance. It is urgently needed to provide a modified catalyst and its preparation method, polyolefin elastomer and its preparation method to improve the above-mentioned problems. Summary of the invention

[0007] The main purpose of the present invention is to provide a modified catalyst and a preparation method thereof, a polyolefin elastomer and a preparation method and application thereof, so as to solve the technical problem of low light transmittance of polyolefin elastomer in the existing gas phase polymerization process technology.

[0008] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a modified catalyst is provided, which comprises a catalyst substrate and a coating layer coated on the outer surface of the catalyst substrate, wherein the catalyst substrate is a metallocene catalyst, the metallocene catalyst comprises a zirconocene chloride main catalyst and a butylaluminoxane co-catalyst, and the coating layer material is a low-carbon olefin homopolymer.

[0009] Furthermore, the thickness of the coating layer is 40-140 μm, and the modified catalyst is in a granular form, and its particle size D50 is 130-330 μm.

[0010] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a method for preparing a modified catalyst is provided, which comprises: subjecting a catalyst substrate, olefins, nitrogen and a solvent to a micropolymerization reaction to form a coating layer on the outer surface of the catalyst substrate to obtain a modified catalyst.

[0011] Furthermore, the olefin is selected from one or more of ethylene, propylene or 1-butene; the solvent is preferably selected from one or more of cyclopentane, propane, butane, pentane or hexane; the temperature of the micropolymerization reaction is preferably 25~45°C, the reaction pressure is 0.2~0.5MPa, and the reaction time is 20~50min.

[0012] According to another aspect of the present invention, a method for preparing a polyolefin elastomer is provided, comprising the step of using a modified catalyst, wherein the modified catalyst is a modified catalyst obtained by the above-mentioned method for preparing a modified catalyst. The method for preparing a polyolefin elastomer comprises: mixing the modified catalyst, ethylene, 1-butene, hydrogen, nitrogen, and a condensing agent in a gas-phase fluidized bed reactor, and then subjecting the modified catalyst and an antistatic agent to a polymerization reaction in the fluidized bed layer of the gas-phase fluidized bed reactor to obtain a polyolefin elastomer.

[0013] Furthermore, the condensing agent is selected from one or more of propane, pentane or cyclopentane, and the amount of the antistatic agent added is 0.001-0.010% of the amount of ethylene added.

[0014] Furthermore, the polymerization reaction temperature is 40-70° C., the polymerization reaction pressure is 1.5-5.5 MPa, the polymerization reaction time is 12-18 h, and the yield of the modified catalyst is 6000-9900 g product / g catalyst.

[0015] According to another aspect of the present invention, a polyolefin elastomer is provided. The polyolefin elastomer is obtained by the above-mentioned method for preparing the polyolefin elastomer.

[0016] Furthermore, the density of the polyolefin elastomer is 0.8750~0.8880g / cm 3 The melt mass flow rate is 4~14g / 10min, the molecular weight distribution width PDI is 2.0~2.3, and when the thickness of the polyolefin elastomer is 0.5mm, the transmittance at a wavelength of 290~380nm is 85~90%, and the transmittance at a wavelength of 380~1100nm is 90~93.5%.

[0017] According to another aspect of the present invention, there is provided an application of a polyolefin elastomer in the field of POE pure adhesive film or EPE structure photovoltaic adhesive film, and the polyolefin elastomer is the above-mentioned polyolefin elastomer.

[0018] The polyolefin elastomer prepared by the present invention has improved uniformity of comonomer insertion into molecular chain segments and improved light transmittance of the product, thus making its industrial application prospect broader. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be clearly and completely described below in combination with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0020] According to the background technology part of the present invention, the polyolefin elastomer in the existing gas phase polymerization process technology has the technical problem of low light transmittance. Based on this, the present invention provides a modified catalyst, which includes a catalyst substrate and a coating layer coated on the outer surface of the catalyst substrate, wherein the catalyst substrate is a metallocene catalyst, the metallocene catalyst includes a zirconocene chloride main catalyst and a butylaluminoxane co-catalyst, and the coating layer material is a low-carbon olefin homopolymer.

[0021] At present, the microstructural factors that affect the light transmittance of polyolefins are mainly the crystallinity, grain size and uniformity of distribution of comonomer alpha-olefin. When the insertion of comonomer alpha-olefin on the ethylene molecular chain is more uniform, its distribution uniformity is higher, and its grain size is more uniform, so that its light transmittance is higher. However, when the insertion of comonomer alpha-olefin on the ethylene molecular chain is more uneven, its distribution is uneven, and the content of large crystals is higher or more fine and small broken crystals are more, and the grain size is uneven, so that the light transmittance is poor. The present invention adopts a novel modified catalyst to reduce the activity of the original catalyst, slow down the degree of instantaneous implosion produced by adding the catalyst for polymerization reaction, so that the comonomer can be more orderly and uniformly distributed on the main chain of the ethylene molecule, so as to improve the light transmittance. Specifically, the modified catalyst provided by the present invention is obtained by further coating on the basis of the catalyst matrix metallocene catalyst to obtain a coating layer, and the coating layer material is a low-carbon olefin homopolymer, which can further improve the structural stability of the catalyst. The modified catalyst solves the problem that in the gas phase preparation process of polyolefin elastomers, ethylene and α-olefin raw materials instantly explode upon encountering unmodified catalysts, thereby causing uneven insertion and distribution of comonomers on the ethylene molecular chain.

[0022] In a preferred embodiment, the coating layer has a thickness of 40 to 140 μm, the weight average molecular weight of the coating layer material is 100 to 2000 g / mol, and the modified catalyst is granular, and its particle size D50 is 130 to 330 μm, thereby further improving the light transmittance of the polyolefin elastomer. Preferably, the metallocene catalyst is a commercially available metallocene catalyst, the main catalyst component of which is zirconocene chloride, and the co-catalyst is butylaluminoxane. Among them, in the metallocene catalyst, the mass proportion of zirconium element is 0.48%, and the mass proportion of aluminum element is 19.2%.

[0023] A metallocene catalyst is used as a catalyst matrix to further improve the catalytic performance of the modified catalyst.

[0024] Another aspect of the present invention provides a method for preparing a modified catalyst, which comprises: subjecting a catalyst substrate, olefins, nitrogen and a solvent to a micropolymerization reaction to form a coating layer on the outer surface of the catalyst substrate to obtain a modified catalyst.

[0025] The skilled person in the art firstly conducts a micro-polymerization reaction on the catalyst substrate, olefin, nitrogen and solvent to form a coating layer on the outer surface of the catalyst substrate to obtain a modified catalyst. The modified catalyst can moderately suppress its initial activity during the subsequent polymerization reaction in the reactor, thereby further improving the light transmittance of the product.

[0026] In a preferred embodiment, the olefin is selected from one or more of ethylene, propylene or 1-butene; the solvent is selected from one or more of cyclopentane, propane, butane, pentane or hexane; the temperature of the micropolymerization reaction is 25~45°C, preferably 35~40°C, the reaction pressure is 0.2~0.5MPa, and the reaction time is 20~50min, preferably 30~40min.

[0027] On the other hand, the present invention also provides a method for preparing a polyolefin elastomer, comprising the step of using a modified catalyst, wherein the modified catalyst is a modified catalyst obtained by the above-mentioned method for preparing a modified catalyst. The method for preparing a polyolefin elastomer comprises: mixing the modified catalyst, ethylene, 1-butene, hydrogen, nitrogen, and a condensing agent in a gas-phase fluidized bed reactor, and then subjecting the modified catalyst and an antistatic agent to a polymerization reaction in the fluidized bed layer of the gas-phase fluidized bed reactor to obtain a polyolefin elastomer.

[0028] A person skilled in the art first mixes a modified catalyst, ethylene, 1-butene, hydrogen, nitrogen and a condensing agent in a gas phase fluidized bed reactor, and then carries out polymerization reaction in a fluidized bed layer of the gas phase fluidized bed reactor to obtain a polyolefin elastomer. The polyolefin elastomer has excellent optical properties and high light transmittance.

[0029] In a preferred embodiment, the polymerization reaction temperature is 40-70°C, the polymerization reaction pressure is 1.5-5.5 MPa, the polymerization reaction time is 12-18 h, and the yield of the modified catalyst is 6000-9900 g product / g catalyst, thereby preparing a polyolefin elastomer product with better performance.

[0030] Another aspect of the present invention provides a polyolefin elastomer, which is obtained by the above-mentioned preparation method of polyolefin elastomer. Its density is 0.8750-0.8880 g / cm 3 The melt mass flow rate is 4~14g / 10min, the molecular weight distribution width PDI is 2.0~2.3, and when the thickness of the polyolefin elastomer is 0.5mm, the transmittance at a wavelength of 290~380nm is 85~90%, and the transmittance at a wavelength of 380~1100nm is 90~93.5%.

[0031] The polyolefin elastomer prepared in the present invention has the following microstructure: a) The content of comonomer 1-butene is 11.0~15.0mol%; b) Molecular chain segment ternary sequence distribution: [EEE]=0.600~0.700, [EEB]=0.170~0.180, [EBE]=0.110~0.160, [BEB]=0.012~0.024, [BBE]=0.005~0.045, [BBB]=0~0.003; c) Average ethylene sequence length nE = 8.7~9.4; d) 1-butene average sequence length nB = 1.05~1.12; Among them, [EEE] represents the fraction of ethylene triads; [EEB] represents the fraction of ethylene diads; [EBE] represents the fraction of ethylene meta-sequences; [BEB] represents the fraction of butene-1 meta-sequences; [BBE] represents the fraction of 1-butene diads; [BBB] represents the fraction of 1-butene triads. The microstructure of the above polyolefin elastomer characterizes the uniformity of the inserted molecular segments of 1-butene.

[0032] On the other hand, the present invention also provides an application of a polyolefin elastomer in the field of POE pure adhesive film or EPE structure photovoltaic adhesive film, and the polyolefin elastomer is the above-mentioned polyolefin elastomer.

[0033] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0034] Example 1 The catalyst substrate, olefin, nitrogen and solvent are subjected to micropolymerization reaction to form a coating layer on the outer surface of the catalyst substrate to obtain a modified catalyst. The catalyst substrate is a metallocene catalyst, the olefin is propylene, the solvent is cyclopentane, the micropolymerization reaction is carried out in a tubular container with a capacity of 10L, the micropolymerization reaction temperature is 40°C, the pressure is 0.35MPa, and the reaction time is 30min. The coating layer material is a low-carbon olefin homopolymer with a weight average molecular weight of 2000g / mol, the coating layer thickness is 140μm, and the modified catalyst is granular with a particle size D50 of 330μm.

[0035] The modified catalyst, ethylene, 1-butene, hydrogen, nitrogen and condensing agent are mixed in a gas phase fluidized bed reactor, and then the modified catalyst and antistatic agent are taken to the fluidized bed layer of the gas phase fluidized bed reactor for polymerization reaction to obtain a polyolefin elastomer. Among them, the polymerization temperature is 68°C, the polymerization pressure is 1.55MPa, the catalyst yield is 9300g product / g catalyst, the amount of antistatic agent added accounts for 0.0012% of the amount of ethylene added, the condensing agent is cyclopentane, the polymerization time is 12h, and a polyolefin product is obtained. The density of the polyolefin elastomer product is 0.8870g / cm 3The melt mass flow rate MFR (190℃, 2.16kg) is 4.9g / 10min, and the molecular weight distribution width PDI is 2.25; the content of comonomer 1-butene in the product is 11.0mol%, and the molecular chain segment ternary sequence distribution is: [EEE]=0.699, [EEB]=0.173, [EBE]=0.111, [BEB]=0.012, [BBE]=0.007, [BBB ]=0.002; the average sequence length of ethylene nE=9.3, the average sequence length of 1-butene nB=1.07, where [EEE] represents the fraction of ethylene triads; [EEB] represents the fraction of ethylene diads; [EBE] represents the fraction of ethylene meta-sequences; [BEB] represents the fraction of butene-1 meta-sequences; [BBE] represents the fraction of 1-butene diads; [BBB] represents the fraction of 1-butene triads. The product was pressed and sampled to obtain a polyolefin product with a thickness of 0.5 mm. The transmittance of the product at a wavelength of 290~380nm was 87.2%, and the transmittance of the product at a wavelength of 380~1100nm was 90.1%. The product is used for blending in the raw materials of photovoltaic encapsulation film POE, with a blending ratio of 20%.

[0036] Example 2 The only difference from Example 1 is that the micropolymerization temperature is 38°C, the pressure is 0.20 MPa, the coating layer material is a low carbon olefin homopolymer, the weight average molecular weight is 1400 g / mol, the coating layer thickness is 105 μm, and the modified catalyst is granular, and the particle size D50 is 260 μm.

[0037] The polymerization temperature is 58°C, the polymerization pressure is 2.05MPa, the catalyst yield is 8400g product / g catalyst, the amount of antistatic agent added is 0.0045% of the amount of ethylene added, the condensing agent is pentane, and the polymerization time is 14h. The density of the polyolefin elastomer product is 0.8826g / cm 3 The melt mass flow rate MFR (190℃, 2.16kg) is 9.7g / 10min, and the molecular weight distribution width PDI is 2.12; the content of comonomer 1-butene in the product is 12.23mol%, and the molecular chain segment ternary sequence distribution is: [EEE]=0.675, [EEB]=0.171, [EBE]=0.121, [BEB]=0.017, [BBE]=0.014, [BBB]=0.002; the average ethylene sequence length n E =9.1, average sequence length n of 1-butene B=1.09. Wherein, [EEE] represents the fraction of ethylene triads; [EEB] represents the fraction of ethylene diads; [EBE] represents the fraction of ethylene meta-ads; [BEB] represents the fraction of butene-1 meta-ads; [BBE] represents the fraction of 1-butene diads; [BBB] represents the fraction of 1-butene triads. The product was pressed into a sheet to obtain a sample with a thickness of 0.5 mm. The transmittance of the sample at a wavelength of 290-380 nm was 87.7%, and the transmittance of the sample at a wavelength of 380-1100 nm was 90.9%. The product is used for blending in the raw materials of photovoltaic encapsulation film POE, with a blending ratio of 30%.

[0038] Example 3 The only difference from Example 1 is that the micropolymerization temperature is 35°C, the reaction time is 40 min, the coating layer material is a low carbon olefin homopolymer with a weight average molecular weight of 800 g / mol, the coating layer thickness is 75 μm, and the modified catalyst is granular with a particle size D50 of 200 μm.

[0039] The polymerization temperature is 45°C, the polymerization pressure is 4.5MPa, the catalyst yield is 6000g product / g catalyst, the amount of antistatic agent added is 0.009% of the amount of ethylene added, the condensing agent is propane, and the polymerization time is 18h. The density of the polyolefin elastomer product is 0.8785g / cm 3 The melt mass flow rate MFR (190℃, 2.16kg) is 13.9g / 10min, and the molecular weight distribution width PDI is 2.10; the content of comonomer 1-butene in the product is 14.40mol%, and the molecular chain segment ternary sequence distribution is: [EEE]=0.607, [EEB]=0.170, [EBE]=0.159, [BEB]=0.022, [BBE]=0.042, [BBB]=0; the average ethylene sequence length n E =8.8, average sequence length n of 1-butene B =1.11. Wherein, [EEE] represents the fraction of ethylene triads; [EEB] represents the fraction of ethylene diads; [EBE] represents the fraction of ethylene meta-ads; [BEB] represents the fraction of butene-1 meta-ads; [BBE] represents the fraction of 1-butene diads; [BBB] represents the fraction of 1-butene triads. The product is pressed into sheets to obtain a polyolefin elastomer with a thickness of 0.5 mm. The transmittance of the product at a wavelength of 290-380 nm is 89.3%, and the transmittance of the product at a wavelength of 380-1100 nm is 92.8%. The product is used for blending in the raw materials of photovoltaic encapsulation film POE, with a blending ratio of 35%.

[0040] Example 4 The only difference from Example 2 is that the micropolymerization olefin is 1-butene, the reaction time is 40 min, the coating layer material is a low carbon olefin homopolymer with a weight average molecular weight of 1200 g / mol, the coating layer thickness is 110 μm, and the modified catalyst is granular with a particle size D50 of 270 μm.

[0041] The catalyst yield was 7500 g product / g catalyst, and the polymerization time was 16 h. The density of the polyolefin elastomer product was 0.8854 g / cm 3 The melt mass flow rate MFR (190℃, 2.16kg) is 10.0g / 10min, and the molecular weight distribution width PDI is 2.18; the content of comonomer 1-butene in the product is 11.83mol%, and the product is pressed into sheets to obtain a polyolefin elastomer with a thickness of 0.5mm. The transmittance at a wavelength of 290-380nm is 88.2%, and the transmittance at a wavelength of 380-1100nm is 91.5%. The product is used for blending in POE raw materials for photovoltaic encapsulation film, and the blending ratio is 25%.

[0042] Example 5 The only difference from Example 3 is that the micropolymerization olefin is ethylene, the reaction time is 35 min, the coating layer material is a low carbon olefin homopolymer with a weight average molecular weight of 500 g / mol, the coating layer thickness is 40 μm, and the modified catalyst is granular with a particle size D50 of 130 μm.

[0043] The polymerization pressure was 5.05 MPa, the catalyst yield was 6800 g product / g catalyst, and the density of the polyolefin elastomer product was 0.8755 g / cm 3 The melt mass flow rate MFR (190℃, 2.16kg) is 14.0g / 10min, and the molecular weight distribution width PDI is 2.02; the content of comonomer 1-butene in the product is 14.93mol%, and the thickness of the obtained polyolefin elastomer is 0.5mm after tabletting. The transmittance at a wavelength of 290-380nm is 89.4%, and the transmittance at a wavelength of 380-1100nm is 93.3%. The product is used for blending in POE raw materials for photovoltaic encapsulation film, and the blending ratio is 45%.

[0044] Comparative Example 1 The only difference from Example 1 is that the micropolymerization reaction temperature is 60°C, the feed ratio of propylene is increased, the coating layer material is a low-carbon olefin homopolymer with a weight average molecular weight of 4300 g / mol, the coating layer thickness is 260 μm, and the modified catalyst is granular with a particle size D50 of 570 μm.

[0045] The catalyst yield was 8200 g product / g catalyst, the mass ratio of the antistatic agent added to ethylene was 0.0030%, and the polymerization time was 16 h. The density of the obtained polyolefin elastomer product was 0.8848 g / cm 3 The melt mass flow rate MFR (190℃, 2.16kg) is 4.90g / 10min, and the molecular weight distribution width PDI is 2.56; the content of comonomer 1-butene in the product is 12.04mol%, and the molecular chain segment ternary sequence distribution is: [EEE]=0.693, [EEB]=0.175, [EBE]=0.093, [BEB]=0.014, [BBE]=0.013, [BBB]=0.012; the average ethylene sequence length n E =9.5, average sequence length n of 1-butene B =1.11, where [EEE] represents the fraction of ethylene triads; [EEB] represents the fraction of ethylene diads; [EBE] represents the fraction of ethylene meta-ads; [BEB] represents the fraction of butene-1 meta-ads; [BBE] represents the fraction of 1-butene diads; and [BBB] represents the fraction of 1-butene triads. The average ethylene sequence length is too long, and the uniformity of 1-butene distribution in the molecular chain segment is poor. The product was pressed and sampled to obtain a polyolefin elastomer with a thickness of 0.5 mm. The transmittance at a wavelength of 290-380 nm was 84.0%, and the transmittance at a wavelength of 380-1100 nm was 87.6%. The product was mixed with 10% of the raw materials of photovoltaic encapsulation film POE, and the transmittance of the obtained photovoltaic film at a wavelength of 380-1100 nm was 88.8%, which could not meet the standard requirement of 90%.

[0046] Comparative Example 2 The only difference from Example 1 is that the polymerization reaction is carried out using an unmodified catalyst, the catalyst yield is 13200 g product / g catalyst, the mass ratio of the antistatic agent added to ethylene is 0.0010%, and the polymerization reaction time is 9 h. The density of the polyolefin elastomer product is 0.8905 g / cm 3 The melt mass flow rate MFR (190℃, 2.16kg) is 5.0g / 10min, and the molecular weight distribution width PDI is 2.72; the content of comonomer 1-butene in the product is 10.2mol%, and the molecular chain segment ternary sequence distribution is: [EEE]=0.772, [EEB]=0.123, [EBE]=0.081, [BEB]=0.007, [BBE]=0.011, [BBB]=0.006; the average ethylene sequence length n E =9.9, average sequence length n of butene-1 B=1.02, where [EEE] represents the fraction of ethylene triads; [EEB] represents the fraction of ethylene diads; [EBE] represents the fraction of ethylene meta-ads; [BEB] represents the fraction of butene-1 meta-ads; [BBE] represents the fraction of 1-butene diads; and [BBB] represents the fraction of 1-butene triads. The product was pressed into sheets to obtain a polyolefin elastomer with a thickness of 0.5 mm. Its transmittance at a wavelength of 290-380 nm was 82.6%, and its transmittance at a wavelength of 380-1100 nm was 85.3%. The transmittance at a wavelength of 380-1100 nm was far lower than the 90% index requirement of photovoltaic adhesive films and could not be used for its blending applications.

[0047] Comparative Example 3 The only difference from Example 3 is that: the polymerization reaction is carried out using an unmodified catalyst, the catalyst yield is 10500g product / g catalyst, the mass ratio of the amount of antistatic agent added to ethylene is 0.0010%, and the polymerization reaction time is 12h. The molecular weight distribution width PDI of the polyolefin elastomer product is 2.44; the content of comonomer butene-1 in the product is 14.20mol%, and the molecular segment ternary sequence distribution is: [EEE]=0.607, [EEB]=0.173, [EBE]=0.143, [BEB]=0.023, [BBE]=0.044, [BBB]=0.010; the average ethylene sequence length n E =8.4, average sequence length n of 1-butene B =1.17, where [EEE] represents the fraction of ethylene triads; [EEB] represents the fraction of ethylene diads; [EBE] represents the fraction of ethylene meta-ads; [BEB] represents the fraction of butene-1 meta-ads; [BBE] represents the fraction of 1-butene diads; and [BBB] represents the fraction of 1-butene triads. The average sequence length of 1-butene is too large, and the distribution uniformity of 1-butene in the molecular chain segment is poor. The product is pressed and sampled to obtain a polyolefin elastomer with a thickness of 0.5 mm. The transmittance at a wavelength of 290-380 nm is 84.7%, and the transmittance at a wavelength of 380-1100 nm is 88.9%. The product is used for blending in photovoltaic encapsulation film POE raw materials, with a blending ratio of 10%, and has low application value.

[0048] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects: From the test results of the above embodiments and comparative examples, it can be found that in the gas phase polymerization process, the uniformity of the comonomer insertion into the molecular chain segment is improved by using a modified catalyst, thereby increasing the POE transmittance; by optimizing the process, improving product quality, and increasing the application ratio of gas phase POE in photovoltaic films, its application prospects are broader.

[0049] Although this specification includes many specific implementation details, these should not be interpreted as limiting the scope of any invention or the scope of protection claimed, but are mainly used to describe the features of the specific embodiments of specific inventions. Certain features described in multiple embodiments in this specification may also be implemented in combination in a single embodiment. On the other hand, the various features described in a single embodiment may also be implemented separately in multiple embodiments or in any suitable sub-combination. In addition, although features may work in certain combinations as described above and even initially claim protection, one or more features from the claimed combination may be removed from the combination in some cases, and the claimed combination may point to a sub-combination or a variation of a sub-combination.

[0050] Thus, specific embodiments of the subject matter have been described. Other embodiments are within the scope of the appended claims. In some cases, the actions recited in the claims can be performed in a different order and still achieve the desired results. In some implementations, multitasking and parallel processing may be advantageous.

[0051] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0052] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A modified catalyst, characterized in that: The modified catalyst comprises a catalyst substrate and a coating layer coated on the outer surface of the catalyst substrate, wherein the catalyst substrate is a metallocene catalyst, the metallocene catalyst comprises a zirconocene chloride main catalyst and a butylaluminoxane cocatalyst, and the coating layer material is a low-carbon olefin homopolymer.

2. The modified catalyst according to claim 1, characterized in that The coating layer has a thickness of 40-140 μm, and the modified catalyst is in a granular form with a particle size D50 of 130-330 μm.

3. A method for preparing a modified catalyst according to claim 1 or 2, characterized in that: The preparation method comprises: subjecting a catalyst matrix, olefins, nitrogen and a solvent to a micropolymerization reaction to form a coating layer on the outer surface of the catalyst matrix to obtain the modified catalyst.

4. The method for preparing a modified catalyst according to claim 3, characterized in that: The olefin is selected from one or more of ethylene, propylene or 1-butene; and / or, The solvent is selected from one or more of cyclopentane, propane, butane, pentane or hexane; and / or, The temperature of the micropolymerization reaction is 25-45° C., the reaction pressure is 0.2-0.5 MPa, and the reaction time is 20-50 min.

5. A method for preparing a polyolefin elastomer, comprising the step of using a modified catalyst, characterized in that: The modified catalyst is the modified catalyst described in claim 1 or 2 or a modified catalyst obtained by the preparation method of the modified catalyst described in claim 3 or 4. The preparation method of the polyolefin elastomer comprises: mixing the modified catalyst, ethylene, 1-butene, hydrogen, nitrogen and a condensing agent in a gas-phase fluidized bed reactor, and then subjecting the modified catalyst and an antistatic agent to a polymerization reaction in the fluidized bed layer of the gas-phase fluidized bed reactor to obtain the polyolefin elastomer.

6. The method for preparing a polyolefin elastomer according to claim 5, characterized in that: The condensing agent is selected from one or more of propane, pentane or cyclopentane, and the amount of the antistatic agent added accounts for 0.001-0.01% of the amount of ethylene added.

7. The method for preparing a polyolefin elastomer according to claim 5 or 6, characterized in that: The polymerization reaction temperature is 40-70° C., the polymerization reaction pressure is 1.5-5.5 MPa, the polymerization reaction time is 12-18 hours, and the yield of the modified catalyst is 6000-9900 g product / g catalyst.

8. A polyolefin elastomer, characterized in that The polyolefin elastomer is a polyolefin elastomer obtained by the method for preparing a polyolefin elastomer according to any one of claims 5 to 7.

9. The polyolefin elastomer according to claim 8, characterized in that The density of the polyolefin elastomer is 0.8750-0.8880 g / cm 3 The melt mass flow rate is 4-14 g / 10 min, the molecular weight distribution width PDI is 2.0-2.3, and when the thickness of the polyolefin elastomer is 0.5 mm, the transmittance at a wavelength of 290-380 nm is 85-90%, and the transmittance at a wavelength of 380-1100 nm is 90-93.5%.

10. An application of a polyolefin elastomer in the field of POE pure film or EPE structure photovoltaic film, characterized in that: The polyolefin elastomer is the polyolefin elastomer according to claim 8 or 9.

Citation Information

Patent Citations

  • Olefin polymer for photovoltaic adhesive film and solution polymerization method thereof

    CN116041598A

  • Polyolefin elastomer and application thereof in photovoltaic packaging film

    CN116789883A

  • Ethylene / α-olefin random copolymer for photovoltaic adhesive film and its application

    CN117567961B

  • Preparation method of polyolefin elastomer POE for photovoltaic packaging

    CN118221858A

  • Kettle adhering prevention preparation method of low-density polyethylene

    CN109438604A

Cited By

  • Polyolefin elastomer for photovoltaic packaging film, preparation method and application

    CN121362278A

  • A polyolefin elastomer for photovoltaic encapsulation films, its preparation method and application

    CN121362278B